Incidência de Hanseniase em menores de 15 anos acompanhados no município de Imperatriz no período de 2004 a 2010 - GORDON, Ariadne Siqueira de Araujo (Universidade Federal do Pará, 2017)
The present study aimed to estimate the overall incidence and rate of leprosy cases in children under 15 years in the city of Imperatriz, analyzing spatial distribution and surveillance actions recommended by the Ministry of Health was a longitudinal study, the incidence of cases of leprosy among children under 15 years, retrospective information with notifications generated by the offense, aside SINAN NET system. Data collection was conducted in the month of June 2012, 284 patients were investigated that were reported in the city of Imperatriz, in the period 2004-2010, as ranked new case, the input mode. The detection rate had its peak in 2005, 83.38 / 100,000 inhabitants. The highest coefficient of patients with Grade Physical Disability (GIF) at diagnosis was in 2004 where it was 39.62%. The coefficient of contacts investigated was 24.44%. As for the detection of new cases were male (51.06%), the color brown (55.65%), aged 10-14 years with 60.22% and schooling average of 6 to 11 years study (59.8%). Regarding the classification and treatment, the type Indefinite (40.13%) and tuberculoid (31.68%) prevailed, and paucibacillary MDT was the treatment of choice in 72.17% of cases reported in the period. Disability was prevalent in 22.2% of all cases. The data confirm the maintenance of hyperendemicity leprosy, especially in children under 15 years, demonstrating the maintenance of the chain of disease transmission, with operating indicators for the surveillance and control program well short of acceptable parameters. The distribution of cases in the county occurred in the area of greatest agglomeration and poor sanitary conditions, represented by District 4, which is composed mainly by neighborhoods Santa Rita, San Jose and New Imperatriz. The number of contacts investigated was considered precarious and operational indicator that assessed degree of disability at diagnosis presented above, specifically with GIF II, demonstrating the late diagnosis of leprosy in children under 15 years in the city.